INFLUENCE OF IMAZETHAPYR ON WEED CONTROL AND PRODUCTIVITY OF GROUNDNUT (ARACHIS HYPOGAEA L.) AND SUCCEEDING SORGHUM (SORGHUM BICOLOR L.) - M. R. UMESH; N. MANJUNATHA; B. N. SHWETHA; N. ANAND (The Bioscan, 2015)
A field experiment was carried out at Raichur, Karnataka with an objective to study the yield response and weed control in groundnut by post emergent application of Imazethapyr 10% SL. Treatments consist of different doses of Imazethapyr, pre emergent pendimethalin and combined application was compared with hand weeding and weedy check. Results indicated that application of pendimethalin 30 EC @ 0.33 kg ai/ha as pre emergent followed by application of Imazethapyr 10% SL @ 0.2kg/ha recorded significantly higher groundnut pod yield (2154 kg/ ha), haulm yield (2648 kg/ha), weed control efficiency (84.9 %). However, it was found significantly on par with application of Imazethapyr 10 % SL @ 0.1 kg ai/ha. Due to higher concentration of Imazethapyr 10 % SL @ 0.1 kg/ha may be preferred over 0.2 kga.i./ha. It can be concluded that application of Imazethapyr 10 % SL @ 0.1 kg ai/ha at 20 DAS was effective to control weeds, enhance productivity of groundnut.